Sustainable use of green waste and CO2 in (electro-)biotechnology - Langsdorf, Alexander; Justus Liebig University Giessen (My University, 2024)
In this work, material recycling methods for green waste in (electro)biotechnology and the bioelectrochemical use of CO2 from flue gas were investigated. The overall aim was to find alternatives to conventional recycling of green waste and ways to reduce CO2 emissions. Initially, it was investigated whether grass clippings, a main component of green waste, can serve as a substrate for fermentation. For this purpose, grass clippings were homogenized and the solids separated. The juice was examined as a medium additive and as the sole medium for the cultivation of Cupriavidus necator pKR-hum. Different sterilization methods for the grass juice and different concentrations as an additive in the fermentation medium were tested. Cupriavidus necator pKR-hum could be successfully cultivated with autoclaved grass juice as the sole growth medium without further additives. A growth rate of 0.43 h-1 was achieved on the grass medium compared to 0.50 h-1 on a conventional LB medium. In addition, 2 mg L-1 of the terpene α-humulene could be produced on the grass medium. As a further utilization method, the extraction of industrially relevant enzymes from green waste was investigated. For this purpose, the common lawn grasses Lolium perenne and Festuca arundinacea were cultivated in the laboratory and a purification scheme for peroxidases was developed. The purified peroxidases were characterized with regard to reaction optima and kinetics and used for the oxidation of the phenolic substances phenol, m-cresol, and 2,4-dichlorophenol for wastewater treatment. The peroxidases of both grasses showed efficient conversion of the substrate 2,4-dichlorophenol. Subsequently, the experiments were repeated with crude extracts of the individual grasses and with a crude extract of real grass clippings. With the crude extract of the real grass clippings, more than 95% of 0.5 mM 2,4-dichlorophenol could be converted within 20 min. Finally, the use of green waste as starting material for electrodes for bioelectrochemical systems was investigated. Grass clippings were carbonized via hydrothermal carbonization and pyrolysis. Electrodes were manufactured from the resulting biochar using a binder and a metallic carrier. Biochar and electrodes were characterized in terms of materials science and electrochemistry. The electrodes were then used in microbial electrosynthesis (MES) with Cupriavidus necator H16 PHB-4 and in a microbial fuel cell (MFC) with Geobacter sulfurreducens and compared with conventional electrodes. As expected, the manufactured electrodes were less suitable for water electrolysis in the MES than conventional metal electrodes. However, the manufactured electrodes showed a similar performance to commercial graphite electrodes in the MFC. In addition, long-term operation of the MFC for more than six weeks could be realized. With regard to real-life application in an industrial environment, the MES was carried out in a cogeneration plant to investigate flue gas as a possible source of CO2. For this purpose, Cupriavidus necator H16 was used to produce the bioplastic polyhydroxybutyrate (PHB) in the MES. The MES was carried out and compared in the laboratory with a clean gas mixture and in the cogeneration plant with real flue gas. The use of flue gas had no detectable effect on either microbial growth or PHB production in comparison to the experiments in the laboratory. In the cogeneration plant, 333 ± 44 mg L-1 PHB could be produced with the MES at a proportion of 43 ± 3% of the dry cell mass. The results demonstrate alternative recycling methods for green waste and CO2 from flue gas, which can contribute to a reduction in the use of fossil resources and CO2 emissions. Overall, this work can support a shift towards a bioeconomy and a circular economy.
Nachhaltige Nutzung von Grünschnitt und CO2 in der (Elektro-)Biotechnologie
Keywords: Bioökonomie; Kreislaufwirtschaft; Elektrobiotechnologie; ddc:570